Dampak Ketergantungan Media Sosial pada Kalangan Dystopian dan Utopian - Irianti, Een (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2017)
Media creates a dependency for its users, it seemed to have become a common sight in media studies at this time. many theories that explain the influence of media on audiences that make audiences are addicted to media such as the theory of hypodermic needles, dependency theory, the theory of cultivation and much more, penguruh media that are considered capable of poisoning the minds of the audience that makes the audience helpless in the face of media exposure , The focus of this article is